Mereological concepts for modelling parthood relations between אלהים and natural phenomena in the Hebrew Bible - Jacobus W. Gericke (Verbum et Ecclesia, 2016)
In the Hebrew Bible, some texts represent what we would call natural phenomena as being in some way related to entities classed to be אלהים in some sense of the Hebrew term; that is, God, gods, divine, deity, etc. Although various perspectives on these relations already exist in the available research on the topic, no philosophical approach to the data has of yet been conceived. In order to facilitate the latter, this study brackets the question as to what the relations between אלהים and natural phenomena in any given biblical context actually were. Yet its contribution lies in the way it aims to offer an introductory overview of some of the potentially relevant core concepts in mereology (parthood theory in metaphysics) that may be of aid in any future attempt at modelling such relations, however they were conceived. Intradisciplinary and/or interdisciplinary implications: This article challenges the tradition of non-philosophical discourse in Old Testament theology, particularly with reference to the relational properties of Yhwh vis-a-vis natural phenomena. Its meta-theoretical application of concepts in formal descriptive mereological analysis represents an interdisciplinary supplementation of current ways of modelling God/World in the text. Keywords: Hebrew Bible; natural phenomena; philosophy; mereology; parthood; relations